Gaya Kepemimpinan Pendeta Perempuan dalam Menyikapi Budaya Patriarkal di Gereja - Sapto Sunariyanti; I Made Priana (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
This paper tries to seek how should the leadership model of woman Pastor be done in response to the impact of patriachal tradition in the Church. In view of this aim, through quality methode this paper firstly investigates the essence of man as God’s image the real and true leader, and secondly explores the character and the influence of patriachal tradition in the Church. Having doing the research, it is found that both man and woman are really mankind so that the two, constitutes human being by nature are called to manifest and to reflex the leadership of God in their life. The first Adam failed to comply and to actualise this mission. That is why the eart rejoices in peace which is designed by God does not come true. Jesus Christ as the second Adam, succes to put into practise the leadership of God. In his such leadership, Jesus does really honor the humanity, love the togetherness or unity and glorify the equality. Patriachal system which has last for years, both outside and inside the Church, is culture that perceives and put man is higher than woman. For this reason, man’s leadership is considered more glorious than woman’s leadership. Since that, in patrichal culture man is preferable and is more accepted to be a leader compare to woman. Up to now, the impact of patriachal tradition does still exsists in the Church. In response to and especially in overcoming the impact of patriachal tradition in the Church, women Pastors are called to be pioneer to practise the leadership of Jesus in their leadership, that is leadership model which honor the humanity, love the togetherness, and glorify the equality.